Compaction technology proceedings of the conference organized by New civil engineer and held in London on 29 October 1987. (Thomas Telford, 1988)
The Department of Transport's sixth edition of 'Specification for Highway Works' shows the most significant developments in compaction technology over the past decade. The specification incorporates major changes including an increase in layer thickness and the acceptance of vibratory rollers.